Regulatory effect of Ganoderma lucidum and its active components on gut flora in diseases - Qin, Xinjie; Fang, Zinan; Zhang, Jinkang; Zhao, Wenbo; Zheng, Ni; Wang, Xiaoe (Frontiers in Microbiology, 2024)
Driven by the good developmental potential and favorable environment at this stage, Ganoderma lucidum is recognized as a precious large fungus with medicinal and nutritional health care values. Among them, polysaccharides, triterpenoids, oligosaccharides, trace elements, etc. are important bioactive components in G. lucidum. These bioactive components will have an impact on gut flora, thus alleviating diseases such as hyperglycemia, hyperlipidemia and obesity caused by gut flora disorder. While numerous studies have demonstrated the ability of G. lucidum and its active components to regulate gut flora, a systematic review of this mechanism is currently lacking. The purpose of this paper is to summarize the regulatory effects of G. lucidum and its active components on gut flora in cardiovascular, gastrointestinal and renal metabolic diseases, and summarize the research progress of G. lucidum active components in improving related diseases by regulating gut flora. Additionally, review delves into the principle by which G. lucidum and its active components can treat or assist treat diseases by regulating gut flora. The research progress of G. lucidum in intestinal tract and its potential in medicine, health food and clinical application were fully explored for researchers.